Social Environmental Correlates of Health Behaviors in a Faith-Based Policy and Environmental Change Intervention. (October 2018) - Hermstad, April; Honeycutt, Sally; Flemming, Shauna StClair; Carvalho, Michelle L.; Hodge, Tarccara; Escoffery, Cam; Kegler, Michelle C.; Arriola, Kimberly R. Jacob
Diet and physical activity are behavioral risk factors for many chronic diseases, which are among the most common health conditions in the United States. Yet most Americans fall short of meeting established dietary and physical activity guidelines. Faith-based organizations as settings for health promotion interventions can affect members at multiple levels of the social ecological model. The present study investigated whether change in the church social environment was associated with healthier behavior at church and in general at 1-year follow-up. Six churches received mini-grants and technical assistance for 1 year to support policy and environmental changes for healthy eating (HE) and physical activity (PA). Socioenvironmental (social support and social norms) and behavioral (HE and PA at church and in general) outcomes were derived from baseline and 1-year follow-up church member surveys ( n = 258). Three of six churches demonstrated significant improvements in all three socioenvironmental aspects of HE. Two of five churches exhibited significant socioenvironmental improvements for PA at follow-up. Church social environmental changes were related to health behaviors at church and in general ( p < .05). Change in social support for HE, social support for PA, and social norms for PA were each associated with three church-based and general behavioral outcomes. Social norms for healthy eating were related to two general behavior outcomes and social norms for unhealthy eating to one general behavioral outcome. Study findings demonstrate that socioenvironmental characteristics are essential to multilevel interventions and merit consideration in designing policy and environmental change interventions.